Resilience and adaptive capacity of Oregon's fishing community: Cumulative impacts of climate change and the graying of the fleet. (April 2021) - Haugen, Brianna I.; Cramer, Lori A.; Waldbusser, George G.; Conway, Flaxen D.L.
Abstract: Although there has been an increase in the research of social-ecological systems, there are still many gaps to understand the effects of change within coastal communities and ecosystems. The drivers of change include climate change, management regulations, demographic shifts, and market trends, and their intersectionality and, ultimately, impacts on commercial fishing communities are poorly understood. The research presented here explores connections between climate change and the increase in the average age of commercial fishermen, referred to as "graying of the fleet". Ultimately, these connections inform our overall objective: to understand how cumulative impacts from these two ongoing phenomena affect the resilience and adaptive capacity of the fishing community. Parsing out the connections may help managers or policy makers more accurately conceptualize future scenarios of community change and simultaneously enables the location of specific target areas for intervention or opportunity. Oral history semi-structured interviews with members of Oregon's fishing community were analyzed and recent climate change projections from the literature were synthesized to parameterize a set of possible scenarios regarding impacts on the fishing community. Results indicate that climate change will likely intensify both the stressors contributing to and the impacts of the graying of the fleet in Oregon. Analysis of the cumulative impacts from climate change and graying of the fleet reveal a greater impact on resilient and adaptive capacities of Oregon's fishing community than analysis of the drivers individually indicates. Therefore, an important implication from this research is the need to evaluate cumulative impacts within these coupled social-ecological systems. Relying on the responsive adaptability of fishing community members alone may not be sufficient, as their resilience and capacity to do so could be limited in the future. Highlights: This article identifies connections between climate change and graying of the fleet in Oregon's (USA) fishing community. Data incorporated oral history semi-structured interviews with 35 fishing community members. Climate change will likely intensify graying of the fleet. Cumulative impacts reveal greater effect on resilience and adaptation than stressors individually indicate. Findings reveal target areas for preparation and action to maintain future resiliency.